Perilaku Kekerasan Aparat Kepolisian Dalam Aksi Demonstrasi Mahasiswa Menurut Perspektif Hukum Dan HAM - Ilham Kurniansyah; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The violent behavior of police officers during demonstrations is an issue that often receives attention from a legal and human rights perspective. Law No. 39/1999 on Human Rights provides a legal basis that supports the protection of the basic rights of every individual, including the right to express opinions, assemble and organize, and the right to be protected from torture and cruel treatment. The purpose of this article is to analyze the factors that led police officers to commit acts of violence against protesting students, and to clarify the legal and human rights monitoring of this issue. This journal uses a normative legal research method, using a statutory approach. The legal materials used are primary, secondary and tertiary legal materials. Using the literature collection method, thus collecting data from the literature then traced, read and understood. The results of this study found that the background of police officers committing violence against students, including provocation, unprofessional officers and environmental conditions at the time of the demonstration. Police officers who are caught committing acts of violence must be reported to be dealt with according to applicable law.